2022
DOI: 10.1177/19375867221092149
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Long-Term Care Facilities: A Rapid Review of Infection Correlates and Impacts on Mental Health and Behaviors

Abstract: Background: Long-term care facilities (LTCFs) with compact, group-living arrangements have become COVID-19 hot spots during the pandemic. Systematic research is needed to understand factors associated with COVID-19 infections in LTCFs and the inadvertent effects of preventive measures adopted by LTCFs. Objectives: This rapid review identifies factors associated with LTCF residents’ COVID-19 infections and the impacts of the pandemic and the corresponding preventive measures on residents’ mental health and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
5
2
4
Order By: Relevance
“…Interestingly, some of these features returned to their baseline values when the lockdown ended, and visits were allowed again. In contrast to some previous studies [ 27 , 28 ], our data do not suggest that lockdown in nursing homes had negative effects on residents’ mental health. It is tempting to speculate that a more peaceful environment caused by social restrictions might contribute to this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, some of these features returned to their baseline values when the lockdown ended, and visits were allowed again. In contrast to some previous studies [ 27 , 28 ], our data do not suggest that lockdown in nursing homes had negative effects on residents’ mental health. It is tempting to speculate that a more peaceful environment caused by social restrictions might contribute to this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies suggesting that the pandemic increased the risk of depressive symptoms among NH residents, 41 we did not find evidence of this. Surprisingly, we found that at the start of the pandemic, the proportion with depressive symptoms significantly declined in AL.…”
Section: Discussioncontrasting
confidence: 99%
“…den Wegfall sozialer Aktivitäten [ 31 ]. Berichtet wurde vor diesem Hintergrund von verstärkten Gefühlen der Isolation, Macht- oder Hilflosigkeit unter den Bewohnenden sowie von Angstzuständen, Depressionen, aggressivem Verhalten und kognitiven Einschränkungen [ 31 , 32 ].…”
Section: Infektionsepidemiologische Und Infektionshygienische Lage In...unclassified
“…werden kann [ 4 , 24 ]. Damit übereinstimmend berichten Ergebnisse von internationalen Studien auch, dass eine hohe Bettenanzahl, limitierte Räumlichkeiten und Mehrbettzimmer zu einem gesteigerten Infektionsrisiko für Bewohnende beitragen [ 5 , 32 ].…”
Section: Infektionsepidemiologische Und Infektionshygienische Lage In...unclassified